Supervision of teaching - Sergiovanni, Thomas J. (Washington St., Alexandria, Virginia : ASCD(Association for Supervision and Curriculum Development), 1982)
The thirteen chapters of this book deal with the varied facets of supervision and give perspective on its history, organizational framework, strategies, models, and future prospects. Part 1 provides a brief historic sketch of supervision in the United States and then moves directly to the issue of evaluating and understanding teaching. The three faces of supervision, the scientific, artistic, and clinical views, are discussed in Part 2. The theory of supervisory practice proposed here seeks to integrate the three views around the theme of helping teachers to be more effective. Part 3 is concerned with the human factor in supervision. Part 4 examines the impact of the curriculum and bureaucratic structure on the process of supervision. Included is an analysis of political and social forces that affect educational policy. Part 5 assesses the possibilities for and new directions in developing the field of supervision and evaluation. A state of the art summary is provided, followed by possibilities for promoting supervisors' development. (Author/MLF)